Relationship between Knowledge and Attitude with Snack Food Selection Behavior among Students of State Elementary School 112164 Talun Manumbok, Labuhan Batu Regency, North Sumatra Province - Riski Agussalim Siregar; Dien Anshari (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Optimal growth and development of school-age children depends on the quality and quantity of their nutritional intake. Meanwhile, the nutritional intake of school-age children is often coloured by snacking behaviour. This study aims to determine the relationship between knowledge and attitudes with snack food selection behaviour in public elementary school students 112164 Talun Manumbok. This study used a quantitative approach with a cross-sectional research design. The research was conducted at 112164 Talun Manumbok public elementary school from January to August 2023. The population in this study were 161 students. The sampling technique used strata sampling of students in grades III, IV, V, and VI, so the research sample was 126. This study collected data using a questionnaire sheet. The independent variables of the study were knowledge and attitude, while the dependent variable was the behaviour of elementary school students in choosing snacks. Data analysis used univariate frequency distribution analysis and bivariate analysis using chi-square test. The results showed that there was a relationship between knowledge and snack food selection behaviour in students at 112164 Talun Manumbok Public Elementary School, with the understanding that students who had better knowledge about snack food selection tended to have better snacks food selection behaviour compared to students who had less good knowledge (PR = 3.38; 95% CI = 1.57-7.26) and there was a relationship between attitude and snacks food selection behaviour in students at 112164 Talun Manumbok Public Elementary School (PR = 5.428 95% CI = 2.417-12.186). The importance of providing education to students is one of the targets that must be implemented and also given good implementation so that children can sort and choose which snacks are good or not for consumption. Keywords: Attitude, Behavior, Knowledge, Snack Food, Students